Durian variety (Durio zibethinus L.) in Kota Bahagia District, South Aceh, Indonesia - Mardudi Mardudi; Eka Selviyanti; Adi Bejo Suwardi (Jurnal Biologi Tropis, 2021)
Durian (Durio zibethinus L.) is one of tropical fruit grown in Southeast Asia and known as King of the fruit. Durian (D. zibethinus) has many varieties with distinctive of morphological characters. The study aim is to explore the diversity of durian varieties in Kota Bahagia sub-district, Aceh, Indonesia. This study was carried out in October-December 2020 in five villages, namely Jambo Keupok, Alur Duamas, Seneubok Alur Buloh, Seneubok Keranji and Beutong. Data collection on the morphological characteristics of durian varieties was carried out through direct field observation of morphology. The data were tabulated and the similarity index was calculated. A total of 18 varieties of durian were found in 5 villages in Kota Bahagia sub-district, i.e. Jantung, Semut, Nanas, Kunyit, Bintang, Tamago, Labu, Bingen, Patai, Jelatang, Jerat, Ampo, Toba, Lilin, Kondo, Limeng, Langsat, dan Gadang Tampok. The highest similarity index value was found in Limeng (Lm) and Patai (Pa) varieties with an association coefficient value of 63.04, while the lowest values were found in Nanas (Na) and Semut (Se) varieties and Kondo (Ko) and Nanas (Na) varieties with an association coefficient of 15.21.